A Prelımınary Revıew On Lean Implementatıon In Dıfferent Sectors And Locatıon - T. Anand, Dr.S.Shanmugapriya (International Journal of Advanced Science and Technology, 2020)
Lean techniques are widely used across many countries in different sectors. The main objective of lean concept is to minimize the wastes generated during any production. Lean management mainly focuses on removing the non-value adding steps in any process of a production. On account of understanding the lean concept in full depth, review has been carried out about lean implementation on different sectors in different countries. From review study, it has been found that implementation of lean methodology offers many benefits to the company such as quality enhancement, on time delivery, clean environment and uninterrupted flow of production process. On personal perspective, extended research can be carried out to identify the lean tools and benefits for the construction sector in full depth to achieve uninterrupted work flow.